Severe immunotherapy-related thrombocytopenia in metastatic bone cancer: a multicenter retrospective case series highlighting early recognition and management - Gao, Qian; Yao, Zhaonong; Yao, Yuhong; Liu, Yunxia; Mao, Jianshui; Li, Binghao (Frontiers in Oncology, 2025)
BackgroundThrombocytopenia (TP) is a rare adverse event (<1%) associated with immune checkpoint inhibitor (ICI) therapy, termed immunotherapy-related thrombocytopenia (irTP). This condition is particularly concerning in patients with metastatic bone cancer due to the increased risk of life-threatening bleeding complications, which may further compromise patient management. Moreover, the scarcity of systematic reports on irTP in this population underscores the need for focused investigation.MethodsWe retrospectively reviewed the clinical records of patients with metastatic bone cancer who received single-agent ICI therapy—specifically, PD-1 inhibitors such as pembrolizumab, penpulimab, and sintilimab—between May 2020 and December 2024 at three tertiary hospitals. Patients who developed severe irTP were included in the analysis.ResultsA total of 94 cases were screened, of which 7 patients (7.45%) were diagnosed with severe irTP. The primary cancer subtypes included melanoma (n = 4), undifferentiated pleomorphic sarcoma (n = 2), and renal clear cell carcinoma (n = 1). All seven patients were undergoing combination therapy with the bone anti-resorptive agent denosumab. The median time to irTP onset was 92 days after the initial ICI administration. Following diagnosis, all patients were hospitalized and received intensive immunomodulatory therapy, supportive care, and meticulous nursing management. While symptoms significantly improved in all cases, long-term follow-up indicated that patients remained stable after discharge. The median duration of hospitalization was 18 days.ConclusionsAlthough irTP is considered rare in the literature, we observed an incidence of 7.45% in our cohort, highlighting a significant clinical concern due to the potential for severe bleeding complications in metastatic bone cancer patients. Timely diagnosis and comprehensive treatment—supported by interdisciplinary collaboration among oncologists, hematologists, and nursing staff—are essential for achieving full recovery. Furthermore, our findings emphasize the need for future research into predictive biomarkers and risk factors for irTP.